Artificial graphite negative electrode material with long circulation and high energy density as well as preparation method and application of artificial graphite negative electrode material

By using the combination technology of sulfonated graphene, secondary coke particles and transition metal salt in the negative electrode material of lithium-ion batteries, a composite product with a core-shell structure is formed, and the problem of insufficient energy density and cycle life of the negative electrode material in the prior art is solved, achieving the effect of high energy density and long cycle life.

CN119569048APending Publication Date: 2025-03-07GUANGDONG DONGDAO NEW ENERGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411637151.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art cannot effectively improve the energy density and cycle life of artificial graphite anode materials of lithium-ion batteries, mainly because the core-shell structure is prone to deform under high compaction density conditions, resulting in shell rupture and capacity loss.

Method used

By mixing sulfonated graphene with secondary coke particles and transition metal salt, ultrasonic dispersion and chemical vapor deposition are performed to form a composite product with a core-shell structure, followed by graphitization to form a clad layer with high graphitization.

Benefits of technology

The high energy density and long cycle life of artificial graphite negative electrode materials are achieved, and the structural stability and cycle performance of the material are enhanced by forming a three-dimensional network cladding with high elasticity and high stiffness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137399170000111
    Figure BDA0005137399170000111
Patent Text Reader

Abstract

The invention provides a long-circulation and high-energy-density artificial graphite negative electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing sulfonated graphene with water, and performing ultrasonic dispersion to obtain sulfonated graphene dispersion liquid; (2) transferring the sulfonated graphene dispersion liquid obtained in the step (1) into a constant-temperature water bath, and adding secondary scorched particles and transition metal salt to obtain turbid liquid; (3) filtering, washing and drying the turbid liquid obtained in the step (2) to obtain graphene-coated secondary scorched particles; (4) performing chemical vapor deposition on the graphene-coated secondary scorched particles in the step (3) and a carbon source to obtain a composite product; and (5) graphitizing the composite product in the step (4) to obtain the artificial graphite negative electrode material. The artificial graphite negative electrode material prepared by the method has the characteristic of isotropy, and has excellent first specific capacity, cycle performance and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to an artificial graphite negative electrode material with a long cycle and high energy density, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have a series of advantages such as high specific capacity, high operating voltage, good safety, and no memory effect, and have been widely used in consumer electronics, electric vehicles, energy storage materials, etc. In recent years, with the continuous development of new energy vehicles, the demand for the power performance of lithium-ion batteries has continued to increase, which has put forward higher and higher requirements on the energy density, safety, and cycle life of batteries.

[0003] Artificial graphite has good compatibility with electrolyte and good cycle performance, and is the preferred negative electrode material for lithium-ion power batteries. In the prior art, a small-particle artificial graphite precursor (such as petroleum coke, needle coke or asphalt coke) is bonded by a binder (such as asphalt or coal tar) to obtain large-particle secondary coke particles, and then high-temperature graphitization can be used to obtain secondary particles of artificial graphite bonded by multiple smaller primary particles of artificial graphite. Finally, asphalt is coated on the surface of the secondary particles of artificial graphite, and the coated asphalt is heat-treated. The artificial graphite negative electrode material prepared by this method includes an artificial graphite core and a shell layer outside the artificial graphite core, and the shell layer is a carbon material coating layer with a low-crystallinity chaotic layer structure. Although this method can enhance the structural firmness of the artificial graphite core and the carbon material shell, prevent the co-embedding of the solvent, and improve the initial specific capacity of the artificial graphite negative electrode material, this method cannot improve the energy density and cycle life of the artificial graphite negative electrode material. The main reasons are: 1) under high compaction density conditions, this core-shell structure is prone to irreversible deformation, causing the shell to rupture and the artificial graphite core to be exposed, resulting in reduced cycle performance; 2) the low-crystallinity carbon coated on the surface has a low reversible capacity, resulting in capacity loss; 3) the compaction density of the low-crystallinity carbon coated on the surface is low, which reduces the energy density of the artificial graphite negative electrode material. Therefore, it is of particular significance to develop an artificial graphite negative electrode material with a long cycle and high energy density. Summary of the invention

[0004] In order to improve the deficiencies of the prior art, the present invention provides an artificial graphite negative electrode material with a long cycle and high energy density, and a preparation method and use thereof. The artificial graphite negative electrode material prepared by the method has the characteristics of isotropy and can have excellent initial specific capacity, cycle performance and energy density.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing an artificial graphite negative electrode material comprises the following steps:

[0007] (1) mixing sulfonated graphene with water and performing ultrasonic dispersion to obtain a sulfonated graphene dispersion;

[0008] (2) transferring the sulfonated graphene dispersion obtained in step (1) into a constant temperature water bath, adding secondary coke particles and transition metal salt to obtain a suspension;

[0009] (3) filtering, washing and drying the suspension obtained in step (2) to obtain graphene-coated secondary coke particles;

[0010] (4) chemically vapor depositing the graphene-coated secondary coke particles of step (3) with a carbon source to obtain a composite product;

[0011] (5) Graphitizing the composite product of step (4) to obtain the artificial graphite negative electrode material.

[0012] According to an embodiment of the present invention, in step (1), the mass of sulfonated graphene added per milliliter of water is (1-1.5) mg, for example, 1 mg, 1.1 mg, 1.2 mg, 1.3 mg, 1.4 mg or 1.5 mg.

[0013] According to an embodiment of the present invention, in step (1), the power and time of the ultrasound are not particularly limited, as long as the sulfonated graphene can be evenly dispersed. Exemplarily, the sulfonated graphene is mixed with water and ultrasonically dispersed for 1-10 hours to obtain a sulfonated graphene dispersion.

[0014] According to an embodiment of the present invention, in step (1), the source of the sulfonated graphene is not particularly defined, and it can be prepared by methods known in the art, or purchased through commercial channels.

[0015] According to an embodiment of the present invention, in step (2), the temperature of the constant temperature water bath is 80-95°C, for example, 80°C, 85°C, 90°C or 95°C.

[0016] According to an embodiment of the present invention, in step (2), the secondary coke particles and the transition metal salt are added under stirring conditions.

[0017] According to an embodiment of the present invention, in step (2), the secondary coke particles are selected from at least one of secondary petroleum coke, secondary needle coke and secondary asphalt coke.

[0018] According to an embodiment of the present invention, in step (2), the median particle size of the secondary coke particles is 12-25 μm, for example, 12 μm, 15 μm, 18 μm, 20 μm or 25 μm.

[0019] According to an embodiment of the present invention, in step (2), the secondary coke particles have a secondary particle structure, and the secondary particle structure is an agglomerate of primary particles. The secondary coke particles can be prepared by methods known in the art, or purchased from commercial sources.

[0020] According to an embodiment of the present invention, in step (2), the secondary coke particles are a carbon material that has not been graphitized.

[0021] According to an embodiment of the present invention, in step (2), the mass ratio of the sulfonated graphene to the secondary coke particles is (0.1-0.4):100, for example, 0.1:100, 0.2:100, 0.3:100 or 0.4:100.

[0022] According to an embodiment of the present invention, in step (2), the transition metal salt is at least one of nitrates, chlorides, sulfates, acetates and oxalates of transition metals; and the transition metal is at least one of iron, cobalt, nickel and chromium.

[0023] According to an embodiment of the present invention, in step (2), the mass ratio of the transition metal salt to the sulfonated graphene is (0.1-0.3):1, for example, 0.1:1, 0.2:1 or 0.3:1.

[0024] According to an embodiment of the present invention, in step (3), the filtration is performed by methods known in the art, such as suction filtration, centrifugal filtration, etc.

[0025] According to an embodiment of the present invention, in step (3), the washing is performed using methods known in the art, such as washing with deionized water.

[0026] According to an embodiment of the present invention, in step (3), the drying temperature is 80-100°C.

[0027] According to an embodiment of the present invention, in step (4), the carbon source is one or more of acetylene, ethylene, methane, ethane, propane and n-butane.

[0028] According to an embodiment of the present invention, in step (4), the flow rate of the carbon source in the chemical vapor deposition is 0.2-2 L / min, for example, 0.2 L / min, 0.5 L / min, 0.6 L / min, 0.8 L / min, 1 L / min, 1.2 L / min, 1.5 L / min, 1.8 L / min or 2 L / min.

[0029] According to an embodiment of the present invention, in step (4), the temperature of the chemical vapor deposition is 500-1000° C., for example, 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., 950° C. or 1000° C. The time of the chemical vapor deposition is 1-6 hours, for example, 2-5 hours, exemplarily 4 hours or 6 hours.

[0030] According to an embodiment of the present invention, in step (4), the chemical vapor deposition is performed under the protection of an inert atmosphere, such as a nitrogen atmosphere or an argon atmosphere. Further, after the chemical vapor deposition process is completed, the obtained product is subjected to a natural cooling process.

[0031] According to an embodiment of the present invention, in step (4), the flow rate of the inert atmosphere in the chemical vapor deposition is 200-800 L / min, for example, 200 L / min, 300 L / min, 400 L / min, 500 L / min, 600 L / min, 700 L / min or 800 L / min.

[0032] According to an embodiment of the present invention, in step (4), the composite product has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes secondary coke particles, the inner shell includes sulfonated graphene, and the outer shell includes carbon nanotubes.

[0033] According to an embodiment of the present invention, in the composite product having a core-shell structure, the core is a secondary coke particle, the inner shell is a sulfonated graphene, and the outer shell is a carbon nanotube.

[0034] According to an embodiment of the present invention, in step (5), the graphitization temperature is 2800-3000°C, for example, 2800°C, 2850°C, 2900°C, 2950°C or 3000°C. The graphitization time is 2-10 hours, for example, 3-8 hours, exemplarily 3 hours, 6 hours. The graphitization can be performed in a graphitization processing furnace.

[0035] According to an embodiment of the present invention, in step (5), during the graphitization process, the secondary coke particles are transformed into an isotropic artificial graphite secondary particle structure; and the sulfonated graphene is transformed into graphene.

[0036] The present invention also provides an artificial graphite negative electrode material prepared by the method.

[0037] According to an embodiment of the present invention, the artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes artificial graphite, the inner shell includes graphene, and the outer shell includes carbon nanotubes.

[0038] According to an embodiment of the present invention, the core is artificial graphite, the inner shell is graphene, and the outer shell is carbon nanotube.

[0039] According to an embodiment of the present invention, the artificial graphite has an isotropic artificial graphite secondary particle structure.

[0040] According to an embodiment of the present invention, the thickness of the shell is 10 nm-20 nm, for example, 10 nm, 12 nm, 15 nm, 16 nm, 18 nm or 20 nm.

[0041] According to an embodiment of the present invention, the thickness of the inner shell is 20 nm-40 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.

[0042] The present invention also provides the use of the artificial graphite negative electrode material, which is used for the negative electrode.

[0043] According to an embodiment of the present invention, a negative electrode is used for a lithium ion battery.

[0044] Beneficial effects of the present invention:

[0045] The invention provides an artificial graphite negative electrode material with a long cycle and high energy density, and a preparation method and application thereof.

[0046] The present invention uses sulfonated graphene that can be uniformly dispersed in water to mix with transition metal salt and secondary coke particles. During the mixing process, the sulfonated graphene can be uniformly coated on the surface of the secondary coke particles, and the transition metal ions can be uniformly attached to the surface of the sulfonated graphene. Subsequently, during the chemical vapor deposition process, the carbon source grows carbon nanotubes in situ on the surface of the sulfonated graphene under the catalytic action of the transition metal ions to obtain a composite product with a core-shell structure. The inner shell and the outer shell as the coating layer in the composite product can be tightly coated on the surface of the secondary coke particles by means of carboxyl groups and sulfonic acid groups. Finally, during the graphitization process, non-carbon atoms (carboxyl groups and sulfonic acid groups) on the sulfonated graphene and the carbon nanotubes are completely removed, the multi-nuclear aromatic ring plane is structuralized, the microcrystals are rearranged, and a highly graphitized coating layer is generated, thereby improving the initial specific capacity of the artificial graphite negative electrode material.

[0047] During the graphitization process, sulfonated graphene forms graphene, and transition metals and graphene synergistically induce secondary coke particles to grow along the graphene layer to form an isotropic artificial graphite secondary particle structure, so that the prepared artificial graphite has a higher degree of graphitization. Finally, a structure in which graphene and carbon nanotubes form a three-dimensional network coating layer with high elasticity and high rigidity on the surface of artificial graphite is obtained, which effectively improves the cycle performance and compaction density of the artificial graphite negative electrode material.

[0048] Moreover, there is a chemical bond between the high elasticity and high stiffness three-dimensional network coating formed by graphene and carbon nanotubes on the surface of artificial graphite and the artificial graphite, which enables the coating to be tightly coated on the surface of artificial graphite, effectively solving the problem of coating shedding caused by the release of carboxyl and sulfonic acid groups. At the same time, due to the high elasticity and high stiffness of the coating, the coating will not deform even under high compaction density conditions, causing the coating to rupture and the artificial graphite matrix to be exposed, resulting in reduced cycle performance and other problems. DETAILED DESCRIPTION

[0049] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0050] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0051] The secondary coke particles used in the following examples and comparative examples were prepared by the following method:

[0052] 1000g needle coke (D 50 =5μm) and 20g asphalt (D 50 =3μm) were mixed evenly, stirred and reacted in a granulation kettle at 600℃ for 5 hours, and cooled to room temperature; then carbonized at 1500℃ for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (D 50 =16μm).

[0053] Example 1

[0054] (1) mixing 1 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a sulfonated graphene dispersion;

[0055] (2) transferring the sulfonated graphene dispersion of step (1) to a constant temperature water bath at 85° C., adding 1000 g of secondary coke particles under stirring, adding 0.16 g of ferric nitrate after stirring for 6 hours, and continuing to stir for 1 hour to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated secondary coke particles;

[0056] (3) placing the graphene-coated secondary coke particles of step (2) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 1 hour in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 800° C. to generate carbon nanotubes, then switching to the introduction of nitrogen, and naturally cooling to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2800° C. for 10 hours, cooling, and obtaining an artificial graphite negative electrode material.

[0057] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 12nm, and the thickness of the inner shell is 23nm.

[0058] Example 2

[0059] (1) mixing 1.2 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 7 hours to obtain a sulfonated graphene dispersion;

[0060] (2) transferring the sulfonated graphene dispersion of step (1) to a 90° C. constant temperature water bath, adding 1000 g of secondary coke particles under stirring, adding 0.2 g of ferric nitrate after stirring for 6 hours, and continuing to stir for 1 hour to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated secondary coke particles;

[0061] (3) placing the graphene-coated secondary coke particles of step (2) in a rotary kiln, and introducing methane at a flow rate of 1 L / min for 2 hours in an argon atmosphere at a flow rate of 100 L / min and an environment of 800°C to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2900°C for 10 hours, cooling, and obtaining an artificial graphite negative electrode material.

[0062] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 14nm, and the thickness of the inner shell is 30nm.

[0063] Example 3

[0064] (1) mixing 1.5 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a sulfonated graphene dispersion;

[0065] (2) transferring the sulfonated graphene dispersion of step (1) to a constant temperature water bath at 85° C., adding 1000 g of secondary coke particles under stirring, adding 0.15 g of ferric nitrate after stirring for 6 hours, and continuing to stir for 1 hour to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated secondary coke particles;

[0066] (3) placing the graphene-coated secondary coke particles of step (2) in a rotary kiln, and introducing ethylene at a flow rate of 1 L / min for 3 h in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 680° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2850° C. for 10 hours, cooling, and obtaining an artificial graphite negative electrode material.

[0067] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 16nm, and the thickness of the inner shell is 34nm.

[0068] Example 4

[0069] (1) mixing 1.3 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a sulfonated graphene dispersion;

[0070] (2) transferring the sulfonated graphene dispersion of step (1) to a constant temperature water bath at 85° C., adding 1000 g of secondary coke particles under stirring, adding 0.24 g of ferric nitrate after stirring for 6 hours, and continuing to stir for 1 hour to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated secondary coke particles;

[0071] (3) placing the graphene-coated secondary coke particles of step (2) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 2 hours in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 750° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2800° C. for 10 hours, cooling, and obtaining an artificial graphite negative electrode material.

[0072] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell is graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 13nm, and the thickness of the inner shell is 25nm.

[0073] Comparative Example 1

[0074] (1) 1000 g of secondary coke particles were graphitized at 2800°C for 10 hours and cooled to obtain artificial graphite.

[0075] (2) mixing 1 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a sulfonated graphene dispersion;

[0076] (3) transferring the sulfonated graphene dispersion of step (2) to a constant temperature water bath at 85° C., adding 1000 g of the artificial graphite of step (1) under stirring, adding 0.16 g of ferric nitrate after stirring for 6 hours, and continuing to stir for 1 hour to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated artificial graphite;

[0077] (4) placing the graphene-coated artificial graphite of step (3) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 1 h in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 800° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain a composite product, and finally immersing the composite product in nitric acid for 6 h, and then washing, dehydrating and drying in sequence to obtain an artificial graphite negative electrode material.

[0078] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell is sulfonated graphene, and the outer shell is carbon nanotubes. The thickness of the outer shell is 12nm, and the thickness of the inner shell is 23nm.

[0079] Comparative Example 2

[0080] The artificial graphite negative electrode material prepared in Comparative Example 1 was graphitized at a high temperature of 2800° C. for 10 hours and cooled to obtain an artificial graphite negative electrode material.

[0081] The graphitization treatment causes the inner shell and the outer shell as the coating layer to fall off, so the artificial graphite negative electrode material formed is essentially a mixture of artificial graphite, graphene and carbon nanotubes.

[0082] Comparative Example 3

[0083] (1) mixing 1 g of sulfonated graphene with 1 liter of water and performing ultrasonic dispersion for 5 hours to obtain a sulfonated graphene dispersion;

[0084] (2) transferring the sulfonated graphene dispersion of step (1) to a constant temperature water bath at 85° C., adding 1000 g of secondary coke particles under stirring to obtain a suspension, filtering the suspension, washing with pure water, and drying to obtain graphene-coated secondary coke particles;

[0085] (3) placing the graphene-coated secondary coke particles of step (2) in a rotary kiln, and subjecting them to high-temperature treatment at 800° C. for 1 hour in a nitrogen atmosphere with a flow rate of 100 L / min, and naturally cooling them to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2800° C. for 10 hours, and cooling them to obtain an artificial graphite negative electrode material.

[0086] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core and a shell; the shell is coated on the surface of the core; the core is artificial graphite, the shell is graphene, and the thickness of the shell is 23nm.

[0087] Comparative Example 4

[0088] (1) 0.16 g of ferric nitrate was dissolved in 1 liter of water and transferred to a constant temperature water bath at 85° C., and 1000 g of secondary coke particles were added under stirring. After stirring for 6 hours, a suspension was obtained. The suspension was filtered, washed with pure water, and dried to obtain secondary coke particles with ferric nitrate loaded on the surface;

[0089] (2) placing the secondary coke particles with iron nitrate loaded on the surface of step (1) in a rotary kiln, and introducing ethane at a flow rate of 1 L / min for 1 hour in a nitrogen atmosphere at a flow rate of 100 L / min and an environment of 800° C. to generate carbon nanotubes, then switching to introducing nitrogen, and naturally cooling to room temperature to obtain a composite product; graphitizing the composite product at a high temperature of 2800° C. for 10 hours, cooling, and obtaining an artificial graphite negative electrode material.

[0090] The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core and a shell; the shell is coated on the surface of the core; the core is artificial graphite, and the shell is carbon nanotubes. The thickness of the shell is 12nm.

[0091] The artificial graphite negative electrode materials of the above embodiments and comparative examples were tested, as described in detail as follows:

[0092] (1) Semi-electric test method:

[0093] The artificial graphite negative electrode material prepared in the embodiment and comparative example: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) was mixed evenly and applied on the copper foil, and the coated electrode was placed in a 120°C vacuum drying oven for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon, the electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio was 1:1:1), the metal lithium sheet was the counter electrode, and the simulated battery test was carried out in a 5V, 10mA Xinwei battery test cabinet, the charge and discharge voltage was 0.01-1.5V, the charge and discharge rate was 0.1C, and the first specific capacity and the first charge and discharge efficiency obtained by the test were listed in Table 1.

[0094] (2) Full battery test method:

[0095] A full battery was assembled using the artificial graphite negative electrode material prepared in the embodiment and the comparative example as the negative electrode, lithium cobalt oxide as the positive electrode, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution as the electrolyte. The battery was charged and discharged at room temperature at a rate of 1C with a voltage range of 3.0-4.2V. The cycle performance obtained from the test is listed in Table 1.

[0096] Table 1 Test results of physical and chemical properties and electrochemical properties of artificial graphite negative electrode materials

[0097]

[0098] It can be seen from Table 1 that, compared with Comparative Example 1, the artificial graphite negative electrode material prepared by the present invention has a high compaction density (high compaction density means high energy density), and the artificial graphite negative electrode material prepared by the present invention has a high first specific capacity, first charge and discharge efficiency and cycle performance.

[0099] Comparative Example 1 adopts the method of first graphitizing the secondary coke particles and then coating the graphene and carbon nanotubes. This method can also rely on the carboxyl and sulfonic acid groups on the graphene to tightly coat the graphene and carbon nanotubes on the surface of the artificial graphite. However, since no graphitization treatment is performed, the non-carbon atom content on the sulfonated graphene and carbon nanotubes is high, and it is still low-crystallinity carbon, which causes the first charge and discharge efficiency and the first specific capacity of the obtained artificial graphite negative electrode material to be low. Moreover, the secondary coke particles are first graphitized, and the transition metal and graphene cannot catalyze the graphitization effect. The prepared artificial graphite has a low degree of graphitization, and the non-carbon atom content on the sulfonated graphene and carbon nanotubes is high, and it is still low-crystallinity carbon, so that the negative electrode material has a lower compaction density.

[0100] Comparative Example 2 is a graphitization treatment performed again on the basis of Comparative Example 1. During the graphitization process, no reaction can occur between graphene and artificial graphite. Only non-carbon atoms (carboxyl and sulfonic acid groups) on sulfonated graphene and carbon nanotubes are removed. Since there is no chemical bond between the coating layer and the artificial graphite, the coating layer will fall off during the graphitization process, thereby obtaining a mixture of artificial graphite, graphene and carbon nanotubes, that is, the coating layer becomes a substance similar to a conductive additive, and its main function in the negative electrode of the battery is to improve the conductivity of the negative electrode, and it does not show good cycle performance. Moreover, since the secondary coke particles have been transformed into artificial graphite at this time, the transition metal and graphene cannot catalyze the graphitization effect during the graphitization process, and the prepared artificial graphite still has a low degree of graphitization, so that the negative electrode material has a low compaction density.

[0101] Compared with Example 1, the preparation process of Comparative Example 3 is to first coat the secondary coke particles with graphene, and then directly perform graphitization treatment without chemical vapor deposition of carbon nanotubes to obtain an artificial graphite as the core and graphene as the shell of the negative electrode material. Since graphene is easily accumulated during the charge and discharge process, the cycle performance of the negative electrode material is rapidly reduced. Moreover, during the graphitization process, since there is no transition metal in the system, it cannot synergistically catalyze the graphitization effect with graphene, so that the graphitization degree of the prepared artificial graphite is reduced, resulting in the obtained negative electrode material having a lower compaction density.

[0102] Compared with Example 1, the preparation process of Comparative Example 4 does not coat the secondary coke particles with graphene, but directly treats the secondary coke particles with chemical vapor deposition carbon nanotubes, and then graphitizes the secondary coke particles to obtain a negative electrode material with artificial graphite as the core and carbon nanotubes as the shell. Although transition metals and carbon nanotubes can also induce the secondary coke particles to grow along the carbon nanotubes to form an isotropic artificial graphite secondary particle structure, and finally form a carbon nanotube coating layer on the surface of the artificial graphite, the two cannot form a synergistic catalytic graphitization effect, so that the graphitization degree of the prepared artificial graphite is reduced, resulting in the obtained negative electrode material having a lower compaction density; not only that, the carbon nanotubes are cylindrical, and the formed coating layer has poor bonding with the artificial graphite, and is easy to fall off during the charge and discharge process, which is easy to cause a reduction in the cycle performance of the negative electrode material.

[0103] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an artificial graphite negative electrode material, comprising the following steps: (1) mixing sulfonated graphene with water and performing ultrasonic dispersion to obtain a sulfonated graphene dispersion; (2) transferring the sulfonated graphene dispersion obtained in step (1) into a constant temperature water bath, adding secondary coke particles and transition metal salt to obtain a suspension; (3) filtering, washing and drying the suspension obtained in step (2) to obtain graphene-coated secondary coke particles; (4) chemically vapor depositing the graphene-coated secondary coke particles of step (3) with a carbon source to obtain a composite product; (5) Graphitizing the composite product of step (4) to obtain the artificial graphite negative electrode material.

2. The preparation method according to claim 1, wherein In step (1), the mass of sulfonated graphene added to each milliliter of water is (1-1.5) mg.

3. The preparation method according to claim 1 or 2, wherein In step (2), the temperature of the constant temperature water bath is 80-95° C.; And / or, in step (2), the secondary coke particles are selected from at least one of secondary petroleum coke, secondary needle coke and secondary asphalt coke; And / or, in step (2), the mass ratio of the sulfonated graphene to the secondary coke particles is (0.1-0.4):100; And / or, in step (2), the transition metal salt is at least one of nitrate, chloride, sulfate, acetate and oxalate of a transition metal; the transition metal is at least one of iron, cobalt, nickel and chromium; And / or, in step (2), the mass ratio of the transition metal salt to the sulfonated graphene is (0.1-0.3):

1.

4. The preparation method according to any one of claims 1 to 3, wherein: In step (4), the carbon source is one or more of acetylene, ethylene, methane, ethane, propane and n-butane; And / or, in step (4), the flow rate of the carbon source in the chemical vapor deposition is 0.2-2 L / min; And / or, in step (4), the temperature of the chemical vapor deposition is 500-1000° C., and the time of the chemical vapor deposition is 1-6 hours; And / or, in step (4), the chemical vapor deposition is performed under the protection of an inert atmosphere, such as a nitrogen atmosphere or an argon atmosphere; And / or, in step (4), the flow rate of the inert atmosphere in the chemical vapor deposition is 200-800 L / min.

5. The preparation method according to any one of claims 1 to 4, wherein: In step (4), the composite product has a core-shell structure; the core-shell structure comprises a core, an inner shell and an outer shell; The inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes secondary coke particles, the inner shell includes sulfonated graphene, and the outer shell includes carbon nanotubes.

6. The preparation method according to any one of claims 1 to 5, wherein: In step (5), the graphitization temperature is 2800-3000° C., and the graphitization time is 2-10 hours.

7. An artificial graphite negative electrode material prepared by the method according to any one of claims 1 to 6.

8. The artificial graphite negative electrode material according to claim 7, wherein The artificial graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes artificial graphite, the inner shell includes graphene, and the outer shell includes carbon nanotubes.

9. The artificial graphite negative electrode material according to claim 7 or 8, wherein: The thickness of the outer shell is 10nm-20nm; the thickness of the inner shell is 20nm-40nm.

10. Use of the artificial graphite negative electrode material according to any one of claims 7 to 9, which is used for a negative electrode.